2016
DOI: 10.1097/jac.0000000000000123
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Community Health Centers in Medicaid Expansion and Nonexpansion States, 2013–2014

Abstract: Using electronic health record data, we examined longitudinal changes in community health center (CHC) visit rates from 2013 through 2014 in Medicaid expansion versus non-expansion states. Visits from 219 CHCs in five expansion states and four non-expansion states were included. Rates were computed using generalized estimating equation Poisson models. Rates increased in expansion state CHCs for new patient, preventive, and limited-service visits (14%, 41%, and 23%, respectively, P<.01 for all), while these rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 13 publications
3
60
1
Order By: Relevance
“…Our findings underscore that CHCs have not experienced a drop‐off in their acceptance of Medicaid patients after Medicaid expansion, and if anything, may be making more primary care available. These results are consistent with recent studies showing how much the volume of care to Medicaid enrollees at CHCs has increased after the ACA . We further add to the literature by providing a direct comparison between appointment availability at CHCs and other primary care practices.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings underscore that CHCs have not experienced a drop‐off in their acceptance of Medicaid patients after Medicaid expansion, and if anything, may be making more primary care available. These results are consistent with recent studies showing how much the volume of care to Medicaid enrollees at CHCs has increased after the ACA . We further add to the literature by providing a direct comparison between appointment availability at CHCs and other primary care practices.…”
Section: Discussionsupporting
confidence: 89%
“…Qualitative studies found that with these additional funds, CHCs were engaging in various delivery system changes, including changing workflow, increasing capacity, and expanding the roles of clinic staff . Medicaid expansion under the ACA is likely to be another key driver of both increased demand and revenue for CHCs in those states that have expanded their programs . To the extent that Medicaid expansion has improved the financial health of CHCs, these changes may have allowed CHCs to focus more services on new Medicaid enrollees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These analyses also revealed a significant 5% increase in overall visit rates in primary care clinics located in states that expanded Medicaid but no significant change in overall visit rates in clinics located in states that opted not to expand Medicaid [17]. OCHIN also assessed changes in visits and services 12 months after ACA Medicaid expansions, discovering that practices in expansion states saw a 14% increase in the number of new patients and provided 41% more preventive services, whereas practices in nonexpansion states saw no change [18]. By bringing data together from primary care practices across the US, these types of analyses can help to inform practice and policy leaders about future workforce needs and increasing demands for primary care services.…”
Section: Tracking Health Insurance Coverage Ratesmentioning
confidence: 99%
“…In 2014, implementation of the Patient Protection and Affordable Care Act (ACA) greatly expanded access to health insurance coverage in the United States, 11-13 and the number of uninsured Americans dropped from 43 million in 2013 to 27 million in 2016. 14 Though the ACA increased opportunities for patients to obtain coverage in 2014, many continue to experience difficulties navigating the complex systems of health insurance enrollment and maintenance.…”
Section: Introductionmentioning
confidence: 99%